Polymer optical fiber sensors for healthcare devices : from material analysis to practical applications - Leal Junior, Arnaldo Gomes (2018)
Advances in medicine and improvements to quality of life have led to an increase in the life expectancy of the general population. An ageing world population has placed demands on the use of assistive technology and in particular towards novel robotic assistance and rehabilitation devices. In order to achieve their functionalities, such robotic devices highly rely on sensors systems, which indicate the necessity of novel sensing solutions to cope with the continuously increasing performance standards of healthcare devices. Besides the electromagnetic field immunity, polymer optical fiber (POF) sensors have additional advantages due to its material features such as high flexibility, lower Young’s modulus (enabling high sensitivity), higher elastic limits and impact resistance. Such advantages are well aligned with the instrumentation requirements of many healthcare devices and in movement analysis. Aiming at these advantages, this Thesis presents the development of POF sensors for healthcare devices. The sensors are developed using two different (and complementary) approaches: (i) Intensity variation-based sensors for low-cost and portable systems; (ii) Fiber Bragg gratings (FBGs), which were inscribed using a femtosecond laser through the direct write plane-byplane inscription method, with the goal of taking advantage of the multiplexing capabilities and high precision of FBGs. Even though POFs presented the aforementioned advantages on sensing applications, polymers by their very own nature are viscoelastic materials, which do not have constant response with stress or strain. Such behavior leads to creep, hysteresis and nonlinearities on POF sensors when the fiber is under stress or strain. In order to compensate these effects, first, a dynamic mechanical analysis is made on two different POF materials: polymethyl methacrylate (PMMA) and cyclic transparent optical polymer (CYTOP) for the characterization of the viscoelastic effects on these fibers. After knowing the material properties, compensation techniques for undesirable effects on POF sensors e.g. hysteresis and nonlinearities, are proposed and validated in different conditions for both intensity variation-based sensors (using PMMA POFs) and FBGs (using CYTOP fibers), obtaining reliable sensors for dynamic measurements of temperature, humidity, strain, force and curvature. Then, both intensity variation- and FBG-based sensors are applied on the instrumentation of exoskeletons, active orthosis and smart walkers. In addition, two instrumented insoles were proposed: one for gait phase estimation in a functional electric stimulation system for gait assistance and the other for plantar pressure monitoring and ground reaction forces assessment using an innovative multiplexing technique for intensity variation-based sensors, resulting in a highly customizable and low-cost system with 15 pressure points. The proposed characterization method for POF materials, compensation techniques and applications in healthcare devices proposed in this Thesis pave the way for novel instrumentation approaches in robotic assistance devices using the proposed flexible sensors, which can be especially desirable not only in the rigid robots presented, but also in soft robotics applications.